Legal Research on The Return of State Financial Losses Through Additional Punishment of Restitution Payments Based on Judge's Consideration (Comparative Study Between Indonesia and South Africa) - Jaco Barkhuizen; Singgih Purnomo; Rina Arum; Dr. Du Ngoc Bich (Jurnal Jurisprudence, 2023)
ABSTRACT Purpose of the study (Tujuan): This study aims to ascertain the judge's consideration in determining additional punishment and describe the problematic implementation of the judge’s consideration (Comparative study of Indonesia and South Africa). Methodology:This study’s type is normative juridical legal research. This approach was employed to obtain a description of the analysis of legal regulations governing restitution as an additional punishment for corruption offenses. The case approach is normative juridical research aimed at studying the application of legal norms or rules carried out in legal practice. Concerning this research, the example of a case to be studied was a corruption case with permanent legal force, namely the Corruption Court Decision (Comparative study between Indonesia and South Africa). Primary data were specifically gathered to answer research questions by interview method. The data analysis technique utilized was a qualitative analysis technique using the interactive method. Results:Based on the results of the aforementioned research, 1) South Africa uses the asset recovery system and involves third parties. In corruption cases in South Africa, the courts seek to ensure that money lost due to corruption is returned to the state. On February 25, 2019, the president of South Africa announced that a special court would be established in accordance with section 2 (1) of the Special Investigative Units and Courts Act, Act No. 74 of 1996, to hear cases arising in court proceedings. 2) In Indonesia, judges have obstacles in interpreting Article 18 of Law No. 31 of 1999 on Corruption Crime Law. The additional restitution punishment is regulated in Article 18 of Law Number 31 of 1999, and the general explanation states, "This law also contains imprisonment for perpetrators of corruption crimes who cannot pay additional punishment in the form of restitution for state losses." However, in practice, the implementation of court decisions on restitution turns out to experience many obstacles because the convicted person does not want to pay and prefers substitute imprisonment or is unable to pay because his property no longer exists. 3) The dualism of sentencing money payment in lieu of additional punishment exists. On the one hand, the judge can decide whether to impose an additional penalty. On the other hand, it is not the case in several corruption cassation decisions, which interpret restitution payments as mandatory, where the judex facti has misapplied the law; it is because the judex facti did not impose restitution payments on the defendant. Applications of this study:Explaining the problematic legal system of returning state financial losses due to corruption crimes through additional compensation payments based on substance factors is contained in Article 18 (1) point b of Law on Corruption Crime. Novelty:The reconstruction of legal substance needs to be prepared so that there is no overlap in the treatment of evidence that uses the instrument  of Article 46 Section (1) point c of the Criminal Procedure Code and Article 33 of Law Number 31 of 1999 on the Eradication of Corruption to create guidelines/technical instructions to determine which alifications / parameters /mechanisms / methods / criteria of evidence that use the instrument from both regulations. Keywords: corruption, judge’s consideration, state financial losses   ABSTRAK Tujuan:Penelitian ini bertujuan untuk mengetahui pertimbangan hakim dalam menetapkan pidana tambahan dan mendeskripsikan problematika pelaksanaan pertimbangan hakim (Studi banding Indonesia dan Afrika Selatan). Metodologi: Jenis penelitian ini adalah penelitian hukum yuridis normatif. Pendekatan ini digunakan untuk memperoleh gambaran tentang analisis peraturan perundang-undangan yang mengatur tentang restitusi sebagai pidana tambahan bagi tindak pidana korupsi. Pendekatan kasus adalah penelitian yuridis normatif yang bertujuan untuk mempelajari penerapan norma atau aturan hukum yang dilakukan dalam praktek hukum. Dalam penelitian ini, contoh kasus yang akan diteliti adalah kasus korupsi yang telah berkekuatan hukum tetap, yaitu Putusan Pengadilan Tindak Pidana Korupsi (Studi Perbandingan antara Indonesia dan Afrika Selatan). Data primer dikumpulkan secara khusus untuk menjawab pertanyaan penelitian dengan metode wawancara. Teknik analisis data yang digunakan adalah teknik analisis kualitatif dengan metode interaktif. Hasil:Berdasarkan hasil penelitian di atas, 1) Afrika Selatan menggunakan sistem pemulihan aset dan melibatkan pihak ketiga. Dalam kasus korupsi di Afrika Selatan, pengadilan berusaha memastikan bahwa uang yang hilang akibat korupsi dikembalikan ke negara. Pada tanggal 25 Februari 2019, presiden Afrika Selatan mengumumkan bahwa pengadilan khusus akan dibentuk sesuai dengan pasal 2 (1) Undang-Undang Unit Investigasi Khusus dan Pengadilan, Undang-Undang No. 74 tahun 1996, untuk mengadili kasus-kasus yang timbul dalam proses pengadilan . 2) Di Indonesia, hakim memiliki kendala dalam menafsirkan Pasal 18 Undang-Undang Nomor 31 Tahun 1999 tentang Undang-Undang Tindak Pidana Korupsi. Pidana tambahan restitusi diatur dalam Pasal 18 Undang-Undang Nomor 31 Tahun 1999, dan penjelasan umumnya menyebutkan, “UU ini juga memuat pidana penjara bagi pelaku tindak pidana korupsi yang tidak dapat membayar pidana tambahan berupa penggantian kerugian negara.” Namun dalam praktiknya, pelaksanaan putusan pengadilan tentang restitusi ternyata banyak mengalami kendala karena terpidana tidak mau membayar dan lebih memilih pidana penjara pengganti atau tidak mampu membayar karena hartanya sudah tidak ada. 3) Adanya dualisme pidana pembayaran uang sebagai pengganti pidana tambahan. Di satu sisi, hakim dapat memutuskan apakah akan menjatuhkan hukuman tambahan. Sebaliknya, tidak demikian halnya dalam beberapa putusan kasasi korupsi yang mengartikan pembayaran restitusi sebagai wajib, di mana judex facti telah salah menerapkan hukum; Hal itu karena judex facti tidak membebankan pembayaran restitusi kepada terdakwa. Kegunaan:Penjelasan sistem hukum bermasalah pengembalian kerugian keuangan negara akibat tindak pidana korupsi melalui pembayaran ganti kerugian tambahan berdasarkan faktor substansi terdapat dalam Pasal 18 (1) huruf b UU Tindak Pidana Korupsi. Kebaruan: Rekonstruksi substansi hukum perlu disiapkan agar tidak terjadi tumpang tindih dalam perlakuan alat bukti yang menggunakan instrumen Pasal 46 Ayat (1) huruf c KUHAP dan Pasal 33 Undang-Undang Nomor 31 Tahun 1999 tentang Pemberantasan.Tipikor untuk membuat pedoman/petunjuk teknis untuk menentukan kualifikasi / parameter / mekanisme/metode /kriteria pembuktian mana yang menggunakan instrumen dari kedua peraturan tersebut. Kata kunci: korupsi, pertimbangan hakim, kerugian keuangan negara